Growth‐dependent phenotype in FasL‐deficient mandibular/alveolar bone. Issue 2 (30th May 2019) - Svandova, Eva; Sadoine, Jeremy; Vesela, Barbora; Djoudi, Amina; Lesot, Herve; Poliard, Anne; Matalova, Eva
Abstract: FASL (CD178) is known for its role in triggering apoptosis, mostly in relation with immune cells but additional functions have been reported more recently, including those in bone development. Examination of postnatal FasL ‐deficient mice ( gld ) showed an increased bone deposition in adult mice when compared with wild types. However, a different phenotype was observed prenatally, when the gld bone was underdeveloped. The aim of the following investigation was to evaluate this indication for an growth‐dependent bone phenotype of gld mice and to search for the 'switch point'. This study focused on the mandibular/alveolar bone as an important structure for tooth anchorage. In vivo micro‐computed tomography (CT) analysis was performed at different stages during the first month (6, 12 and 24 days) of postnatal bone development. In 6‐day‐old gld mice, a decrease in bone volume/tissue volume (BV/TV), trabecular thickness and trabecular number was revealed. In contrast, the 12‐day‐old gld mice showed an increased BV/TV and trabecular thickness in the alveolar bone. The same observation applied for bone status in 24‐day‐old gld mice. Therefore, changes in the bone phenotype occurred between day 6 and 12 of the postnatal development. The switch point is likely related to the changing proportion of bone cells at these stages of development, when the number of osteocytes increases. Indeed, the immunohistochemical analysis of FASL localized this protein in osteoblasts, whereas osteocytes were mostly negative at examined stages. The impact of FASL particularly on osteoblasts would agree with an earlier in vivo observed effect of FASL deficiency on expression of Mmp2, typical for osteoblasts, in the gld mandibular/alveolar bone. Notably, an age‐dependent bone phenotype was reported in Mmp2 ‐deficient mice.